The washback effect of Iranian National University entrance exam (inuee) on pre-university english teaching and learning / Leila Mahmoudi - Mahmoudi, Leila (2014)
Washback effect of a test generally refers to the effect of a test on teaching and learning. Washback is generally known as being either negative or positive (Taylor, 2005). The washback effect of high-stakes tests has been approached and investigated from various perspectives in different contexts and countries. The aims of the current study are: 1. To examine the washback effect of the INUEE on English language teaching as perceived by the teachers. 2. To examine the washback effect of the INUEE on English language learning as perceived by the learners. 3. To examine the washback effect of the INUEE on English language teaching as observed by the researcher. 4. To examine the role of other factors besides the INUEE which contribute to the washback effect of the INUEE on English teaching as perceived by the teachers. 5. To examine the role of other factors besides the INUEE which contribute to the washback effect of the INUEE on English learning as perceived by the learners. The participants of the study were 6 female teachers and 218 female students at two pre-university schools in the city of Ahwaz, Iran. The data were collected through teachers and students’ questionnaires, teachers’ interviews as well as observation of the classes for the six consecutive sessions. In order to better capture and report the nuances of classroom dynamics, all the classroom sessions were audio-video recorded. Existence of various data collection methods made the triangulation of the findings possible. The findings of the study indicated that the teachers and students’ perceptions about the INUEE were mixed; students and teachers with positive attitudes towards the INUEE considered the test as an evaluator of academic knowledge. Moreover, the majority of students viewed the test as a factor that made them study English. However, the teachers and students who held negative perceptions about the INUEE criticized the test on the grounds that it was an evaluator of rote-memorization ability (rather than academic knowledge) and was a main source of anxiety, etc. The students who were critical of the test mainly alluded to its multiple-choice testing format as an inefficient and invalid evaluator of their academic knowledge, as well as the incompatibility of the INUEE and the textbook in terms of level of difficulty. All the teachers and students were unanimously found to hold negative perceptions about the teaching materials. As for the teachers’ perceptions about the English curriculum, the study showed that the teachers had no idea about the existence, and consequently the content and objectives of the curriculum. It was also found that regardless of the teachers and students’ positive or negative perceptions about the INUEE, their processes of teaching and learning were negatively affected not only by the test itself, but also by the factors other than the test. For instance, ‘contextual’ factors such as professional reputation for the teachers and family pressures and peer competitions for the students were among the factors which aggravated the washback effect of the test. The findings of this study could have a number of implications: 1. Observations should be an inseparable part of washback studies. As the study indicated, what teachers claimed to have been doing in their classes in their questionnaires and interviews did not necessarily take place in the natural context of their classes. 2. Given that the national curriculum has devoted a balanced weight towards the four language skills and communicative functions of language, and has emphasized the importance of familiarization of Iranian students with the culture of target-language, the material developers are expected to take the national curriculum as the point of departure for material development. The INUEE also needs to be tailored in order to reflect the language learning goals of the curriculum. Moreover, the test format of the INUEE should be modified. For instance, both the multiple-choice questions as well as open-ended questions should be included in the test. 3. Given the indispensible position of the INUEE in the socio-cultural context of Iran, the test could be capitalized on as an influential instrument to create positive changes on the country’s system of English education. For example, incorporation of the listening skill into the content of the INUEE might probably accentuate its prominence and could entail its practice in the classes by the teachers and students. 4. The cultural awareness of the public towards the genuine values of education and knowledge-seeking should be raised and learning for the sake of genuine learning rather than merely obtaining university degrees should be promoted among the public.